Endodontic and Orthodontic Management of Traumatically Intruded Teeth with Horizontal Root Fracture: A Case Report - Jacobovitz, Marcos (Hindawi Publishing Corporation, 2011)
This report describes the case of an 8-year-old boy that was referred to endodontic and orthodontic treatment after suffering an injury that led to intrusion of the maxillary right permanent central incisor, palatal displacement of the upper right lateral incisor, and root fracture of both central incisors. Both injured teeth were immature and had open apices. The intruded tooth was repositioned by endodontic and orthodontic management. Endodontic therapy was performed in both teeth with periodical changes of calcium-hydroxide-based paste as root canal dressing and introduction of MTA as an apical barrier. The postoperative course was uneventful with clinical and radiographic success up to 3 and 1/2 years of follow up. In the present case, orthodontic repositioning combined with endodontic therapy constitued a viable alternative treatment for intrusive luxations in immature permanent teeth.